Characterization of microsatellite loci in the Himalayan lichen fungus Lobaria pindarensis (Lobariaceae)1. (5th April 2014) - Devkota, Shiva; Cornejo, Carolina; Werth, Silke; Chaudhary, Ram Prasad; Scheidegger, Christoph
Abstract : Premise of the study: Microsatellite loci were developed for the rare, Himalayan, endemic haploid lichen fungus, Lobaria pindarensis, to study its population subdivision and the species' response to forest disturbance and fragmentation. Methods and Results: We developed 18 polymorphic microsatellite markers using 454 pyrosequencing data and assessed them in 109 individuals. The number of alleles per locus ranged from three to 11 with an average of 6.9. Nei's unbiased gene diversity, averaged over loci, ranged from 0.514 to 0.685 in the three populations studied. The cross‐amplification success with related species ( L. chinensis, L. gyrophorica, L. isidiophora, L. orientalis, L. pulmonaria, L. spathulata, and Lobaria sp.) was generally high and decreased with decreasing relationship to L. pindarensis . Conclusions: The new markers will allow the study of genetic diversity and differentiation within L. pindarensis across its distribution. Moreover, they will enable us to study the effects of forest management on the genetic population structure of this tree‐colonizing lichen and to carry out population genetic studies of related species in East Asia.